Eskatologi Islam: Studi Dilalogis Umar bin Khattab dengan Munkar dan Nakir tentang Prosedur Pasca Kematian - Ngatoillah Linnaja; Robingun Suyud El Syam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Among the afterlife in Islamic belief is the grave, where at the beginning of this period it is believed that the soul will be questioned by the angels Munkar and Nakir about his faith and deeds in the world. The purpose of this writing is focused on elaborating on Islamic eschatology in the story of Umar bin Khattab about post-death procedures. Literature research to find out a more in-depth discussion on the topic of post-death procedures by collecting, analyzing, and synthesizing information from books, journals, articles, and other relevant documents, was analyzed content. Findings: The story of Umar bin Khattab with the Angels Munkar and Nakir shows his concern for the welfare of the people. This reflects responsible leadership and is oriented towards the long-term good for all Muslims. Although this particular narrative is not widely documented in classical Islamic texts, it reflects a broader theme in Islamic teachings about the mercy and compassion of Allah and the angels. This story also highlights the exemplary character of Umar and his concern for the welfare of others, even in the afterlife. Conclusion: This story is about a leader who always thinks about the welfare of the people, including those who will face questions in the grave. Novelty: This finding highlights visionary leadership based on the essence of Islam that fosters true happiness in this world and the hereafter, considering the challenges of modern leadership oriented toward the afterlife.